Inpatient hospitalisation and mortality rate trends from 2004 to 2014 in the USA: a propensity score-matched case–control study of hyperkalaemia. Issue 5 (19th May 2022) - Tecson, Kristen Michelle; Baker, Rebecca A; Clariday, Laura; McCullough, Peter A
Abstract : Objective: To study the trends of hyperkalaemia in USA inpatient hospitalisation records with heart failure (HF), chronic kidney disease (CKD), acute kidney injury (AKI) and/or type II diabetes mellitus (T2DM) from 2004 to 2014 with respect to prevalence and inpatient mortality. Design: Observational cross-sectional and propensity score-matched case–control study. Setting: The National Inpatient Sample (representing up to 97% of inpatient hospital discharge records in the USA) from 2004 to 2014 Participants: 120 513 483 (±2 312 391) adult inpatient hospitalisation records with HF, CKD/end-stage renal disease (ESRD), AKI and/or T2DM. Exposure: Hyperkalaemia, defined as the presence of an International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code of '276.7' in any of the first 15 diagnostic codes. Primary and secondary outcome measures: The outcomes of interest are the annual rates of hyperkalaemia prevalence and inpatient mortality. Results: Among 120 513 483 (±2 312 391) adult inpatient hospitalisations with HF, CKD/ESRD, AKI and/or T2DM, we found a 28.9% relative increase of hyperkalaemia prevalence from 4.94% in 2004 to 6.37% in 2014 (p<0.001). Hyperkalaemia was associated with an average of 4 percentage points higher rate of inpatient mortality (1.71 post-matching, p<0.0001). Inpatient mortality rates decreased from 11.49%±0.17% to 6.43%±0.08% and 9.67%±0.13% to 5.05%±0.07% for matched cases with and without hyperkalaemia, respectively (p<0.001). Conclusions: Hyperkalaemia prevalence increased over time and was associated with greater inpatient mortality, even after accounting for presentation characteristics. We detected a decreasing trend in inpatient mortality risk, regardless of hyperkalaemia presence.